Epidemiology of Hepatitis E Virus Infection in Patients on Chronic Hemodialysis - Beladi Mousavi, Seyed Seifollah (Kowsar, 2014)
BACKGROUND: Many studies have been done on the epidemiology of Hepatitis E on general population, but the data among patients with end stage renal disease (ESRD) are few and give conflicting results. OBJECTIVES: The aim of this study was to investigate the prevalence of hepatitis E virus (HEV) infection and its relationship in ESRD patients undergoing maintenance hemodialysis (HD). PATIENTS AND METHODS: This cross-sectional study was carried out on ESRD patients treated with HD in Imam Khomeini Hospital, Ahvaz city, Southwest of Iran. Blood sampling of patients was collected immediately before the dialysis session and the serum were evaluated for anti-HEV IgG titers by enzyme-linked immunosorbent assays. The statistical package for social sciences (SPSS) version 15 software was used for data analysis. RESULTS: Out of 47 ESRD patients, 27 were male (57.4%) and 20 were female (42.6%), with mean age of 55.27 ± 8.1 years. The prevalence of anti-HEV antibody was 10.6 % (five patients, four male and one female). The mean age of HEV positive and negative patients were 58 ± 5.52 and 53.82 ± 15.55 years, respectively without any significant difference (P = 0.058). There also was no significant association between HEV and gender (P = 0.28). The mean time of HD in HEV positive and negative patients were 1224.2 and 1168.5 days, respectively with no significant association (P = 0.88). In addition, there also was no association between HEV and HCV (P = 0.61). CONCLUSIONS: According to the present study, the prevalence of anti-HEV IgG antibody was 10.63 % among chronic HD patients and there was no association between HEV, age, gender, duration of HD and HCV antibody titer.